Canine Mammary Tumors: Risk Factors, Prognosis and Treatments - Benavente, Micaela Andrea (2016)
Mammary tumors are the most common neoplasm in the female dog, with a median age of appearance between 9 and 11 years. They may appear as single or multiple nodules, and posterior mammary glands are more frequently affected than anterior glands. Both benign and malignant tumors may occur in the dog, and according to histological criteria, approximately 50% of the tumors are malignant. Mammary gland tumors tend to be heterogeneous in their pathological characteristics and clinical behavior. Different hormones and growth factors play a key role in the development of this neoplasm, however, the mechanism by which they influence tumor growth and their possible prognostic value are still under study. Besides, new therapeutic options for each particular tumor type are being developed. The aim of this article is to review pathological, prognostic and therapeutic aspects of canine mammary neoplasms.